2015
DOI: 10.1038/cdd.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Stressed neurons protect themselves by a tissue-type plasminogen activator-mediated EGFR-dependent mechanism

Abstract: In the central nervous system, tissue-type plasminogen activator (tPA) has been associated with both pro-death and prosurvival actions on neurons. In most cases, this has been related to exogenous tPA. In the present study, we addressed the influence of endogenous tPA. We first observed an increased transcription of tPA following either in vivo global brain ischemia in rats or in vitro oxygen glucose deprivation (OGD) on mice and rats hippocampal slices. Hippocampal slices from tPA-deficient mice were more sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…CSPG has been implicated in the inhibition of spontaneous axonal plasticity after TBI (30,31). The neurotrophic effects of tPA are thought to be partly mediated by the epidermal growth factor receptor (EGFR) (32,33). As expected, CSPG decreased the length of tau + axons in neurons in a concentration-dependent manner (SI Appendix, Fig.…”
Section: Intranasal Delivery Of Recombinant Tpa Rescues Neurological mentioning
confidence: 56%
“…CSPG has been implicated in the inhibition of spontaneous axonal plasticity after TBI (30,31). The neurotrophic effects of tPA are thought to be partly mediated by the epidermal growth factor receptor (EGFR) (32,33). As expected, CSPG decreased the length of tau + axons in neurons in a concentration-dependent manner (SI Appendix, Fig.…”
Section: Intranasal Delivery Of Recombinant Tpa Rescues Neurological mentioning
confidence: 56%
“…The growth factor domain of tPA confers antiapoptotic capacity through its binding to the EGF receptor. 23,24 However, AG1478 (5 μM), an EGFR tyrosine kinase inhibitor, did not prevent the beneficial effect of tPA during OGD reox ( Figure 5b, 31% of neuronal death for tPA under OGD reox ; 26% for tPA+AG1478 under OGD reox ), excluding a role for EGF receptor. tPA can also interact through its finger domain with LRP-1 (type 1 low-density lipoprotein receptor-related protein) to promote NFκB activation 25 and Akt phosphorylation.…”
Section: Resultsmentioning
confidence: 96%
“…However, more recent studies have shown potential benefits of tPA for the treatment of ischemic stroke. As evidence of its beneficial effects, tPA has been shown to play a critical role in inhibiting neuronal apoptosis and promoting functional recovery in late phase after stroke 1518 . tPA has been shown to exert opposite effects at different time points on the same target 19 (e.g., extracellular matrix, NMDA receptors).…”
Section: Tpa: Biology Thrombolytic Mechanism and Pleiotropic Funmentioning
confidence: 99%